Analisis Model Kepemimpinan Jalur Tujuan (Path Goals) Kajian Kepemimpinan Dalam Lembaga Pendidikan - Sarta Sarta; Anis Zohriah; Anis Fauzi (Journal on Education, 2023)
This study aims to analyze the path goal leadership style in educational institutions. Path Goal Theory is a leadership theory that explains how the behavior of leaders will influence how employees perceive the path between their efforts and goals. Like other situational theories, path goal theory also says that leaders will be successful if they are able to adapt their behavior to the situations they face. For example, directive leadership will be suitable if employees lack experience and knowledge about work, and if work is unstructured and complex. The idea of ​​this theory is that motivation plays an important role in how supervisors and subordinates interact and, based on that interaction, success can be achieved. Path-goal theory presents two basic propositions. First, one of the strategic functions of the leader is to improve the psychological state of subordinates which results in motivation to perform or satisfaction with work. In other words, leaders need to become aware of the necessary steps to in turn increase the intrinsic motivation of subordinates. Second, it asserts that certain situational leader behaviors will achieve a motivational function. Path-goal theory recognizes four leadership behaviors to increase subordinate motivation. The four path-goal leadership styles that serve to provide structure and reward to subordinates are directive, supportive, participative, and achievement-oriented.